MEN TYPE 2B SYNDROME IN A NORMOTENSIVE YOUNG FEMALE WITH INCIDENTALLY DISCOVERED PHAEOCHROMOCYTOMA - Kamil, Mohd Firdaus Mohamad; Azman, Siti Sanaa Wan; Ali, Masliza Hanuni Mohd; Mohamad, Ms Siti Hartinie; Mohamed, Hussain; Muda, Nor Hisham (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Phaeochromocytomas (PC) account for up to 5–25% of adrenal incidentalomas. Some PC patients, especially those with an adrenal incidentaloma, are asymptomatic and have normal blood pressure. The frequency of incidentally discovered normotensive phaeochromocytomas is increasing owing to better accessibility of imaging procedures. These tumours may be linked to certain genetic syndromes, such as Multiple Endocrine Neoplasia (MEN) type 2B, a rare condition caused by the RET proto-oncogene mutation, and includes a range of clinical manifestations such as phaeochromocytomas, medullary thyroid carcinoma and mucosal neuromas. CASE A 34-year-old female who had undergone total thyroidectomy for medullary thyroid carcinoma (MTC) was referred for an incidental right adrenal mass from CT staging. She had no paroxysms of headache or palpitations, no family history of MTC, pheochromocytoma and MEN-related diseases. She was normotensive. Physical examinations revealed mucosal neuromas on the tongue, buccal mucosa, lips, and eyelids. No marfanoid habitus present. Laboratory results showed normal serum calcium (2.57 mmol/L), but a 24-hour urine metanephrine was four times the upper limit of normal, along with borderline elevation of normetanephrines. The adrenal CT revealed an indeterminate right adrenal mass measuring 2 × 2 × 3 cm with peripheral calcifications suggesting pheochromocytoma. Left lymph node and carotid sheath biopsy were reported as features consistent with ganglioneuroma. The patient is scheduled for a right retroperitoneoscopic adrenalectomy. The unifying clinical presentations are consistent with MEN 2B Syndrome. However, genetic panel testing was not done due to financial constraints. CONCLUSION This case underscores the importance of considering genetic syndromes, such as MEN type 2B, in patients with incidental findings of pheochromocytomas, even when the patient is normotensive. Early diagnosis and genetic testing can help guide management, including surveillance for other tumours associated with MEN type 2B and early intervention. Further research is needed to explore the clinical presentation of pheochromocytomas in normotensive patients.